Pengembangan E-modul Matematika Berbasis STEAM Untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Kelas IV Sekolah Dasar - Sholikah, Ridhotul Abadi; Kowiyah , Kowiyah (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2024)
This research aims to add learning resources that can stimulate students' critical thinking by developing a STEAM-based mathematics e-module on measurement material. The method used is Research & Development with the ADDIE model. The feasibility and effectiveness of the product are the main focus in research involving material, media, language and educator experts. Through the validation process, the product is tested on students to test its effectiveness. The research results show a) based on the overall percentage of material experts 84.89%, media experts 94.90%, language experts 78.67%, and teacher validation 96.52% so that the e-module is suitable for use. b) e-modules are quite effective from the post-test results with 46.4% in improving critical thinking skills. The STEAM-based mathematics e-module with measurement material was declared suitable for use and quite effective for students.